History of semiotic ideas: between chroniclers and innovators - Portela, Jean Cristtus (Estudos Semióticos, 2018)
The article consists of an epistemological and historical study about the historiography of the Semiotics of discourse and has the objective of proposing a critical reading of the way by which semioticians have focused on Semiotics history. From reflections developed within the scope of the history of linguistic ideas (S. Auroux) and the frame of historical and conceptual studies of Semiotics (J.-C. Coquet, M. Arrivé, A. Hénault, H. Parret, E. Landowski, C. Zilberberg, S. Badir, among others), it analyzes historical approaches on the Semiotics of discourse, concerning its objectives, its methodology and its object, distinguishing two types of historical works that remain current until the moment amongst semioticians (that of the chroniclers and that of the innovators) and, at the same time, proposes the minimum fundamentals of a meta-historiography of semiotic inspiration.